Studi keragaan kapal pengawas hiu 02 di Pangkalan Pengawasan Sumber Daya Kelautan dan Perikanan Bitung: The Performance of the HIU 02 Surveillance Ship in the PSDKP Bitung - Efrayanto Lumuhu; Kawilarang Warouw Alex Masengi; Fransisco Philep Theodorus Pangalila; Revols Dolfi Christian Pamikiran; Lefrand Manoppo; Hesky Stefy Kolibu; Haryadi Wijaya (Universitas Sam Ratulangi, 2023)
The objectives of this study are to determine the amount of fuel consumption within one hour at 600, 1200, and 1700 rpms; describe the operation of the vessel's main engine; and describe the systems in the vessel's main engine. A patrol vessel serves to carry out surveillance and law enforcement against vessels engaged in illegal fishing. In conducting surveillance, the patrol vessel is supported by a main engine, which is a component that propels the vessel. The operation, the main engine requires fuel oil (BBM) to drive the engine. The research findings indicate that : (1) the fuel consumption of the main engine within one hour is 54 liters at 600 rpm, 108 liters at 1200 rpm, and 170 liters at 1700 rpm; (2) the operation of the main engine is carried out by checking the fuel, lubricating oil, cooling water, and opening the fuel valve and seawater valve before starting the engine. Then, turn the engine contact switch from OFF to ON position to enable the ship to move, and to stop the engine, reduce the engine throttle and turn the contact switch from ON to OFF position, and then close the opened valves; (3) The systems in the main engine include the electric starting system, fuel system, wet lubrication system, and closed cooling system.